Analysis of tracheobronchial foreign bodies - Adhikari, P; Shrestha, BL; Sinha, BK; Baskota, DK; Sharma, NR (Journal of Institute of Medicine Nepal, 2008)
Background: To analyze the type and site of tracheo-bronchial foreign bodies in patients admitted in the department of ENT-Head and Neck surgery (ENT-HNS) of TU Teaching Hospital. Methods: Medical records of 41 cases admitted in the department of ENT-HNS, TU Teaching Hospital, Kathmandu between April 2004 to October 2006 for the management of suspected foreign bodies in tracheobronchial tree were analysed retrospectively. It was found that rigid bronchoscopy was performed in all 41 cases and foreign bodies were removed from 36 cases. In the five cases where foreign body was not found, were excluded from the study. Results: There were 83.3% children and 16.6% adults. Most common type of foreign body found in children were vegetative (63.3%) where as in adults beetle nut (50.0%) and metallic foreign bodies (50.0%) were found. Majority of foreign body was found to be lodged in the right main bronchus (56.7%) in children. Whereas, in adults foreign bodies (66.7%) were found in the left main bronchus. Radiological confirmation of the foreign body could be made only in 8 cases (22.2%). All patients had an uneventful postoperative period except two (5.5%) who died during postoperative period after removal of foreign bodies from trachea. Conclusion: In children, foreign body is more common in right bronchus where as in adults it is more common in left bronchus. Only 22.2% foreign bodies could be seen in plain X-ray. In unresolved pneumonia high index of suspicion of foreign body in tracheobronchial tree must be made and diagnostic bronchoscopy should be performed. Keywords: Vegetative foreign body, metallic foreign body, rigid bronchoscopy The full text of this paper is available at Journal of Institute of Medicine website